BASIC CONCEPTS AND PRINCIPLES OF INSURANCE (Spectrum Journal of Innovation, Reforms and Development, 2023)
Insurance done increase in the process insurance of participants differently insurance interest manifestation to be to insurance belongs to of objects diversity, insurance of events wide scope and another factors with depends has been complicated specific relationships sum surface will come. That's it relationship with she is or this concrete insurance relationships special terminology using reflection carry on necessity is natural.